Profile of Serum Folate Levels in Various Severity Degrees of Psoriasis Vulgaris Patients at Murni Teguh Memorial Hospital Medan - Natascya Putri Siburian; Rudyn Reymond Panjaitan; Joseph Partogi Sibarani (SEAN Institute, 2026)
Psoriasis vulgaris is a chronic inflammatory disease characterized by keratinocyte proliferation and excessive immune system activation. Folic acid plays a role in DNA synthesis and cell division processes. Keratinocyte hyperproliferation in psoriasis can affect serum folic acid levels, but previous studies have shown varying results. The aim of this study was to determine the serum folic acid level profile in patients with various degrees of psoriasis vulgaris severity at Murni Teguh Memorial Hospital in Medan. This was a cross-sectional study with a sample size of 11 respondents at Murni Teguh Memorial Hospital in Medan. The results showed that the majority of respondents were in the early-to-late adulthood age group (54.5%) with an average serum folate level of 9.1 ng/mL. Based on gender, the majority of respondents were female (63.6%) with an average serum folate level of 9.5 ng/mL. Based on the severity of vulgaris psoriasis, most respondents were in the mild category (72.7%) with an average serum folic acid level of 9 ng/mL, while those in the moderate category (27.3%) had an average level of 8 ng/mL. It can be concluded that all respondents (100%) in this study had serum folic acid levels in the normal range.